Hubungan Kepribadian Narsistik dengan Perilaku Impulsive Buying Mahasiswa (PTS) X Bandar Lampung - Yuni Zulaiha; Setriani Setriani; Meilia Ishar (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the relationship between narcissistic personality and impulsive buying behavior among students who shop online at a Private University or locally Perguruan Tinggi Swasta (PTS) in Bandar Lampung City.Methodology: The research was conducted among Islamic Education students at a private university in Bandar Lampung City. A non probability sampling method with a systematic sampling technique was employed. Data were collected using two psychological scales, the Narcissistic Personality Scale and the Impulsive Buying Scale. A simple correlation analysis technique was used to determine the relationship between the two variables.Results: The results indicated a significant positive relationship between narcissistic personality and impulsive buying behavior, with a correlation of determination (R²) showed that narcissistic personality accounted for 34% of the variance in impulsive buying behavior, while the remaining 66% was influenced by other factors.Conclutions: The findings suggest that narcissistic personality traits are an important predictor of impulsive buying behavior among online-shopping students, highlighting the need to consider personality dimensions in strategies to manage impulsive purchasing.Limitations: This study was limited to one private university and used a simple quantitative analysis approach; therefore the findings may not be generalisable to a wider population or other educational settings.Contributions: This study contributes to psychology and consumer behaviour by examining the influence of narcissistic traits on students' impulsive buying. The findings provide a reference for future research and practical strategies to address impulsive buying among young consumers.